Penyelesaian Pelanggaran Administrasi Pemilu oleh Bawaslu - Lefteuw, Maksimus; Pattiasina, Lidia Priscilla (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: The legal issues in this writing include how are the legal arrangements regarding the settlement of general election administration by Bawaslu and how to resolve election disputes by Bawaslu. Purposes of the Research: This writing aims to find out and analyze how to resolve violations of general election administration by Bawaslu. Methods of the Research: The research method used is normative, that is, research that primarily examines positive legal provisions and legal principles, explain and predicts in the direcrion of future legal developments Results Originality Findings of the Research: The findings of this study prove that in legal arrangements regarding the settlement of election administrative violations by Bawaslu and the settlement mechanism that in an effort to resolve administrative violations, Bawaslu has the authority to resolve administrative violations in accordance with the provisions of the Bawaslu laws and regulations and the General Election Commission. The settlement mechanism based on the Election Law is not explained significantly but it is explained that non-criminal violations are administrative violations and these violations are reported and followed up by Bawaslu and the General Elections Commission.